LOCAL GOVERNMENT`S ROLE IN THE SUSTAINABLE TOURISM DEVELOPMENT OF A DESTINATION - Brokaj, Rezarta (European Scientific Journal, ESJ, 2014)
Recent statistical information indicates that tourism is one of the largest and fastest growing industries in the world (WTO, 2013). The tourism industry plays a prominent part in the economic development strategies of many developing countries. However, the tourism industry can also be viewed as a destructive force, associated with negative externalities such as the loss of natural landscapes, congestion, environmental and cultural degradation. These problems are more likely to be exacerbated where there is a lack of well-designed planning and effective management of tourism development. Academic literature has examined how the development of tourism destinations involves collaborative relationships between the various actors that participate in tourism development. Using the case study of tourism in the city of Vlora, this paper argues that it is essential to understand the role, responsibilities and benefits of both three most important stakeholders of a destination from sustainable tourism practice and policy and also how they respond to its adoption. The aim of this paper is to gain a better understanding of the evolutionary processes of tourism development towards sustainability in Albania according to the main stakeholders: local governance, tourism enterprises and local community, focusing mostly on the challenges and weaknesses that expand within and beyond the boundaries of local government and hinder the enhancement of Vlora as an important tourist destination in Albania. The research data-gathering methods: literature reviews, secondary data and semi-structured interviews are all used to gain insights into the core research questions. Each method feeds into and is strengthened by the others and their combination. The results of this study point out the fact that there are a wide range of factors that constrain the Vlora tourism industry from adopting more sustainable tourism practices. All of these factors play a crucial role in materialization the actions of all stakeholders in relation to sustainable tourism principles.